Fortalecimiento de la habilidad matemática: visualización en estudiantes de grado séptimo - González González, Elizabeth (Universidad Antonio Nariño, 2023)
In the last times, the study and development in the thinking and mathematical Reasoning skill, is object of many investigations today, because it allows to the students discover the relationship and connections among the mathematical objects, use mental math in space figures, match and interpret visual and necessary images to understand complex topics like in Algebra, Geometry and also solve difficult problems in the Basic Education in a best way. This way the viewing is very important because it helps to develop unknown ideas and to achieve advance understandings.